Sunflowers and Other Plants - Morgan, Sally (London Belitha, 2001)
Looks in detail at the life cycle of the sunflower, and includes additional information about the life cycles of other plants. Suggested level: primary
Include Color Illustration, Glossary and Index
Keywords: Sunflowers--Life cycles -- Plant life cycles -- Sunflowers